Quality Factors and Customer Satisfaction For Sustainable Community Development - Wakhid Slamet Ciptono (Universitas Trisakti, 2006)
The purpose of this investigation is to explore a research on the relationships between quality factors and customer satisfaction for sustainable community development. The unique contributionUnits (SBU) managers from the Indonesia's oil and gas industry and the use of Importance-performance Ratings and Factor Analysis to determine the link between quality factors (external quality and internal quality and customer satisfaction for sustainable community development. The empirical analysis found that the link between Quality factors and customer satisfaction is linear in the keep-Up Good Work Quadrant. The survey indicates that is much room for improvement in the quality factors and customer satisfaction for the sustainable community development as shown in the difference between importance and performance scores. These scores indicate mismatched importance and performance of quality factors. Conversely, low difference values indicate that managers set appropriate quality factors with respect to customer satisfaction and deploys sustainable community development accordingly. Ideally, the difference measure should equal zero.